Preparation and characterization of enteric microparticles by coacervation. (July 2013) - Thomas, Steffi; Chong, Yin Ning; Chaw, Cheng Shu
<x xml:space="preserve">Abstract</x> The aim of this study was to produce cinnarizine loaded Eudragit® L100-55 microparticles by coacervation technique in order to achieve pH responsive drug release using hydroxypropyl methycellulose (HPMC) as stabilizer. The effect of enteric polymer: HPMC ratio on properties of microparticles was investigated with regard to particle size distribution, morphology, yield, encapsulation efficiency, in vitro drug release profiles and interaction between cinnarizine and Eudragit® L100-55. High drug encapsulation efficiency was seen in all microparticles. Particle diameter increased when the enteric polymer content was higher relative to HPMC. In vitro dissolution studies demonstrated that the drug release from the microparticles was dependent upon enteric polymer: HPMC ratio and particle size distribution. At the ratio of at least 3.75:1 of enteric polymer: HPMC, drug release was suppressed most significantly in low pH (hydrochloric acid as medium) while rapid drug release was observed in pH 7.4.